2016
DOI: 10.4172/2471-9935.100003
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Responsive Hydrogels:Construction and Applications

Abstract: IntroductionAs a kind of smart materials, responsive hydrogels exhibit the rapidly responsive ability and sharp volume phase transitions according to the external stimuli from environment. Hydrogels demonstrate large-scale volumetric changes in response to small levels of stimuli. To the best of our knowledge, the most typical external stimuli factors related to responsive behaviors of smart hydrogels are pH [1][2][3][4][5], temperature [6][7][8], light [9][10][11] and multi-factors [12][13][14][15][16]. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…They demonstrated almost complete selectivity of release following stimulation with ultrasound. Similar hydrogels and polymers have been developed that are temperature [42][43][44] , pH [45][46][47][48] or light responsive [49][50][51] .…”
Section: Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated almost complete selectivity of release following stimulation with ultrasound. Similar hydrogels and polymers have been developed that are temperature [42][43][44] , pH [45][46][47][48] or light responsive [49][50][51] .…”
Section: Drug Deliverymentioning
confidence: 99%
“…The heat range in which this occurs is referred to as the upper and lower critical solution temperatures [42][43][44] . Unfortunately, it can often be challenging to control temperature or photoenervation in-vivo so pH responsive polymers tend to be a bit more popular.…”
Section: Ritter Et Al Largely Pioneered the Development Of Thermo-rementioning
confidence: 99%
“…Furthermore, the diversified properties and applications of hydrogels have reasoned thousands of research articles focusing on various aspects. Numerous review articles on the different broad-spectrum are also found based on applications [49][50][51][52] and hydrogel types [53][54][55][56][57] . However, a critical review addressing the techniques to tailor different functional properties and governing mechanisms of responsive behavior are yet to be amassed into a single frame.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, organic dyes have been applied as colorants in textiles dyeing, sensitizers in dye‐sensitized solar cells, emitting layer in organic light‐emitting diode, photovoltaic charge separation, and charge‐carrier transporter in field‐effect transistors 5 . With the development of dye stuff chemistry, the chemical structure‐optical property relationship has been elucidated for all kinds of dyes such as cyanine (Cy), rylene, and aggregation‐induced emission dye (AIEgen) 6‐8 . Encountering the vastly increasing biomedical demands, organic dyes have recently been applied for health‐related applications such as in vivo imaging, disease diagnosis, and treatment 9 .…”
Section: Introductionmentioning
confidence: 99%